1995
DOI: 10.1111/j.1528-1157.1995.tb00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differing Dosages of Vigabatrin (Sabril) on Cognitive Abilities and Quality of Life in Epilepsy

Abstract: Vigabatrin (VGB) prevents seizures by irreversible inhibition of gamma-aminobutyric acid (GABA) transaminase and a resulting increase in GABA levels. We evaluated the cognitive and quality-of-life (QOL) effects of VGB in a double-blinded, add-on, placebo-controlled, parallel group dose-response study of patients with focal epilepsy whose complex partial seizures (CPS) were difficult to control. In a single investigation, patients were randomly assigned to placebo (n = 40), 1 g VGB (n = 36), 3 g VGB (n = 38), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 93%
“…Patients who attained TGB monotherapy improved in the areas of adjustment and mood (67), a change attributable most likely to discontinuation of previous AEDs. Similarly, several investigations of the cognitive and behavioral effects of VGB have shown no or only minimal impairment, and even some evidence of improvement (68)(69)(70)(71)(72). Psychosis and depression have been repeatedly described with VGB, both in adults and in children (73)(74)(75).…”
Section: Newer Aedsmentioning
confidence: 93%
“…None of the studies reported a priori sample size calculation, and may potentially have been underpowered. In two trials, some doses of VGB exceeded the recommended limit, 153,168 and in three further studies, the number of participants completing the study was unclear. 51,152,169 In one of these, trials over 20% of follow-up data were classified as missing.…”
Section: Tgbmentioning
confidence: 99%
“…38,51,87,[152][153][154]168,169 Twenty-two studies were parallel superiority trials and 10 were crossover trials. No studies of adjunctive OXC reported QoL outcomes.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The instrument has been validated against external criteria, including professional and significant-other ratings of psychosocial functioning (27). It has also been translated into several languages (37-41) and used as an outcome measured in several clinical trials (20)(21)(22). Although the WPSI contains subscales that reflect many of the domains of HRQL, it was constructed as a measure of psychological and social adjustment in persons with epilepsy.…”
Section: Resultsmentioning
confidence: 99%